The Jordanian Bank's Compliance Practice on Custom and Letter of Credit - Al-Amaren, Emad Mohammed; Aletein, Sultan Ibrahim (Faculty of Law, Universitas Sebelas Maret, 2022)
The Uniform Custom and Practice (UCP 600), has defined letter of credit as: “Any arrangement, however, named or described, that is irrevocable and thereby constitutes a definite undertaking of the Issuing Bank to honour a complying presentation